The Atmospheric Sciences - Peltier, W. (Geoscience Canada, 1993)
Abstract Current research in the atmospheric sciences has come to be heavily influenced by the growing need to understand increasingly evident changes taking place in the earth system. The research agenda includes issues involving processes that span the full range of space and time scales relevant to atmospheric behaviour. A common the me that links the separate strands of this activity concerns the interrelationships among distinct atmospheric sub-systems and, indeed, the mechanisms through which the atmosphere as a whole interacts with other elements of the total environment. I expect this trend to become increasingly evident in thefuture. It is imperative, however, that as these interdisciplinary activities develop, the core research areas continue to receive strong support, for it is upon them that the integrity of the field will continue to rely.